Enhancing match official performance: a forward-thinking approach for football evolution - Castagna, C.; Krustrup, P.; Mohr, M.; Póvoas, S. (Science and Medicine in Football, 2024)
The future of football demands more from players and referees due to heightened match intensity and frequency. To optimize performance and health, collaboration among sport scientists, coaches, and medical staff is crucial. However, match officials often lack the same support as elite players, hindering their development. Granting professional status to referees, implementing evidence-based training, and adopting gender-inclusive methods are vital. Coping with future challenges requires better career support and economic conditions for officials, along with research to enhance their performance and health.